Dimensions of job satisfaction of library professionals: a qualitative exploration - Haque, Mahbubul; Karim, A.N. Mustafizul; Muqtadir, Afia; Anam, Shahriyar (Maryland Institute of Research, 2012)
This research is aimed at investigating the underlying causes of job satisfaction of the library staff at a large public university in Malaysia. A qualitative methodology, namely, hermeneutic phenomenology, approach is undertaken with Herzberg’s two-factor theory employed in designing the interview protocol. Twelve full-time librarians take part in the interviews for this purpose. Despite in a few cases, the study reveals a general concord with Herzberg’s reasoning vis-à-vis the factors leading to staff satisfaction or dissatisfaction. One striking feature of the finding relates to the religious values and environment contributing to the staff satisfaction to a great extent. Some recommendations and possible future research areas are also suggested.